The prognostic and predictive value of homologous recombination deficiency status in patients with advanced stage epithelial ovarian carcinoma after first-line platinum-based chemotherapy - Xu, Yiqing; Chen, Yi-Ju Amy; Wu, Yunhong; Saverimuthu, Angela; Jadhav, Archana; Bhuiyan, Rehana; Sandler, Jason; Yio, Jiang; Kumar, Vivek (Frontiers in Oncology, 2024)
Objective: Homologous recombination comprises series of interrelated pathways that repairs double-stranded DNA breaks and inter-strand crosslinks. It provides support for DNA replication to recover stalled or broken replication forks. Compared with homologous recombination proficiency (HRP), cancers with homologous recombination deficiency (HRD) are more susceptible to DNA-damaging agents, such as platinum agents, and have better disease control. Methods: Patients diagnosed with stage III/IV ovarian cancer, earlier stages with recurrence, who received adjuvant chemotherapy after debulking surgery with known HRD status were eligible. Results: 44 patients included. 21 in the HRD group (including 8 with germline mutations) and 23 in the HRP group. HRD group comprised predominantly of serous carcinoma (95.2%). Mucinous (n=3) and clear cell (n=1) cases were solely found in the HRP group. When comparing HRD and HRP groups, stage III/IV disease was 66.7% and 91.3 % (p=0.064). Patients who were optimally debulked to no residual disease was 90.0% and 72.7% (p=0.243). Late line use of PARP inhibitors was 33.3% and 17.4% (p=0.303). Median PFS was 22.5 months (95% CI, 18.5 -66.6) and 21.5 months (95% CI, 18.3-39.5) (p=0.49). Median platinum free interval (PFI) was 15.8 months (95% CI 12.4-60.4) and 15.9 months (95% CI 8.3-34.1) (p=0.24). Median OS was 88.2 months (95% CI 71.2-NA) and 49.7 months (95% CI 35.1-NA) (p=0.21). PFS of germline BRCA mutations (n=5) was 54.3 months (95% CI 23.1-NA) and 21.5 months (95% CI 18.3-39.5) in the HRP group (p=0.095). PFI difference was 47.7 months (95% CI 17.6-NA) in the BRCA mutation group, and 15.9 months (95% CI 12.4-60.4) in HRP, showing statistical significance (p=0.039); while the median OS was NA and 49.7 months (95% CI 35.1-NA) respectively (p=0.051). When including two additional patients with somatic BRCA mutations to the germline BRCA mutation carriers, the median OS is NA (95% CI 73, NA) versus 49.7 months (95% CI 35.1, NA) for HRP (p=0.045). Conclusions: HRD was not associated with longer PFS or PFI in advanced ovarian cancer who received first line adjuvant platinum-based chemotherapy. Its role as a prognostic marker for OS is suggested, particularly in the subgroup with germline and somatic BRCA mutations.